Innovating to Survive: The Mediating Role of Innovation Capability on the Sustainable Performance of Culinary MSMEs - Edi Edi; Nayla Amanda (Jurnal Strategi dan Inovasi Bisnis, 2026)
Background: Culinary MSMEs face a structural paradox in developing regions where rapid growth is met with asymmetric and fluctuating government infrastructure support. Previous studies often overlook the holistic integration of psychological and structural factors in driving innovation and business resilience.   Purpose: This study aims to empirically examine the mediating role of innovation capability in the relationship between infrastructure support, capacity building, and self-efficacy on the sustainable performance of culinary MSMEs.   Methods: An explanatory quantitative approach was employed using a saturated sample of 180 culinary MSMEs receiving government interventions in Dompu Regency. Primary data were collected via structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS.   Results: The analysis reveals that capacity building and self-efficacy significantly enhance sustainable performance through the mediation of innovation capability. However, infrastructure support directly impacts sustainable performance but fails to trigger innovation capability, thus negating its mediation effect. Furthermore, self-efficacy emerged as the most dominant driver of innovation capability among MSME owners.   Conclusion: Innovation capability is a crucial mediator that translates managerial capacity and psychological resilience into sustainable performance. Meanwhile, physical infrastructure serves merely as a passive structural resource that ensures direct operational stability without stimulating adaptive innovation.